Dengue seroprev alence and factors influencing it among student of MARA University Of Technology, Shah Alam , 1999 - Zaiton Nasir,; Osman Ali, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Dengue haemorrhagic fever is a vector-borne disease, which remains a serious public health problem in this country. A cross-sectional study was conducted at MARA University of Technology, Shah Alam from August to September 1999. The objectives are to measure the prevalence rate of IgG seroconversion towards dengue among student and to identify factors influencing it. A total of 218 respondents were selected by random sampling from a list of students staying in the residential colleges. Blood sample were taken and serological test was carried out to measure level of IgG. Statistical Package For Social Science Version 8~0 was used to analyse the data obtaine-d. Results showed that prevalence rate of IgG seroconversion are 49.1 %. Of this positive results, only 0.9% had history of symptomatic dengue infection. Other respondents had asymptomatic infections. Male students have twice higher risk of getting positive IgG seroconversion compared to female (p<0.05). Students above 21 years of age have 3 times higher risk compared to those below 21 years of age (p<0.05). Those students originated form urban areas have 4 times higher risk than students from rural areas (p<0.05). In general, knowledge, attitude and practice among student were good, however these factors were not significantly orrelated to IgG seroconversion (p>0.05). In conclusion, individual factors such as knowledge, attitude and practice alone could not stop the increase of seroconversion rate, because there are other factors that play major roles in influencing the development of seroconversion. These include environmental factors, inter agencies involvement and communities. There for it is suggested that further study should be carried out looking into environmental factors not directly related to students such as septic tanks, roof gutter, trees and construction areas. Further prospective study is also suggested to see the interaction between environment and behaviour among students who have negative IgG seroconversion.